Parallel corpora as texts in a TSP context. An argumentative approach - Daniela Corina Ionescu (Bucharest Working Papers in Linguistics, 2007)
The present paper aims at proposing several ways of selecting and typologising specialized texts according to different criteria, such as thematic content, genre criteria, or structural discursive differences. This approach follows the current views on discourse structure and the theory of parallel corpora. The texts that make up a corpus of targeted discourse pieces share several properties but they also serve a different purpose, which is the author’s communicative intention to make the information or comments structured in the text relevant in some specific way to readership. It is precisely this relevant markedness of such texts that constitutes the core of the present paper.